The role of LMX differentiation in relationship between LMX and perceptions of OPPA - Miaochun, Chen (2017)
The aim of this study is to investigate the relationships between leader member exchange (LMX), LMX differentiation and perceptions of organizational politics in performance appraisal(OPPA). Data were collected by students enrolled in Master of Human Resource Management and administered a self-reported questionnaire to employees working in different sectors of diverse countries (N=99). The measurement of LMX differentiation is relative LMX (RLMX) and LMX variance (LMXD) By analyzing the data from subordinates, it was found that LMX is negatively correlated with perceptions of OPPA, and RLMX moderates this relationship. LMXD as direct effect is also negatively related to perceptions of OPPA, however, it does not moderate the relation between LMX and perceptions of OPPA. Limitations, future research perspectives and practical implications are further discussed.